Building Customer Citizenship Behavior from Relationship Quality and Perceived Value Perspective in Online Transportation Service - Tatik Suryani; Indra Listyarti (JURNAL SOSIAL HUMANIORA (JSH), 2020)
Recently, Customer Citizenship behavior (CCB) become research focus in marketing. But, not many research focus on the antecedent of this variable from marketing behavior perspective. The research objective is to examine the effect of Relationship Quality and Perceived Value on CCB in online transportation services and Customer Satisfaction as the mediation in this relationship. Research involved 400 online transportation customers in Indonesia who used minimum three times in this transportation. By using Partial Least Square (PLS), the result found that Relationship Quality has a significant positive effect on Customer Satisfaction and CCB, Perceived Value has positive significant effect on Customer Satisfaction and has not significant effect CCB. It means that for strengthen CCB, the online transportation should create customer satisfaction. Research also found that Customer Satisfaction has a positive effect on CCB. The implication of the research is online transportation should improving the relationship quality and value for creating customer satisfaction for strengthening CCB. Customer satisfaction is the important conditions for improving CCB.